Efektivitas Air Kelapa Muda Hijau Dengan Buah Pisang Terhadap Perubahan Tekanan Darah Pada Lansia Di Pemenang Barat - Ulandari, Ni Nyoman Santi Tri; Cahyono, Wahyu; Islami, Bq. Izzatul; Sulistyani, Endah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The elderly population in the west pemenang village is 473 elderly, and elderly with hypertension in west Pemenang that reaches up to 46 elderly. Based on the preliminary interview with the elderly with hypertension in west pemenang, most of them only had therapy with medical medicine and not woth alternative therapy sch as green young coconut water and banana fruit. They don’t know the benefit of using coconut water and banana fruit for hypertension treatment. This research is aimed at determining the effectiveness of green young coconut and banana fruit on the change of blood pressure of elderly in west pemenang. This reasearch is quasy-experimental study with on group pre test and post test design. The populations were all 46 elderly with hypertension living in west pemenang. The samples were 30 elderly selected through purposive sampling. The data were collected through the instruments of observation sheet and documentation. The research showed that young coconut water affected the change of blood pressure of elderly. In the group of banana fruit therapy, blood pressure of elderly also had the change. Both groups together had changes in blood pressure. Banana fruit therapy is more effective comparing to other. It is inferred that both types of therapy are effective in decreasing blood pressure of elderly.